TINGKAT PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN LUBUK LARANGAN DI SUNGAI BATANG TEBO KABUPATEN BUNGO PROVINSI JAMBI - Rini Hertati (Jurnal Inovasi Penelitian, 2021)
The management of the prohibition pit of Tepian Napal, Tanah Grow District, Bungo Regency is managed by the local community together from formation to opening, which is carried out in a traditional manner in accordance with existing local wisdom. The research method used is survey and interview, the data analysis used is SWOT analysis. Collecting data, primary data and secondary data. From the results of the study, it was found that the value of community participation was in the low category with a value of 30.00% and the value of stakeholder participation was 7.48%. For internal scores with a score of 0.88 and an external score of 0.59.